End point surrogacy in first-line chronic lymphocytic leukemia - Simon, Florian; Ligtvoet, Rudy; Robrecht, Sandra; Cramer, Paula; Kutsch, Nadine; Fürstenau, Moritz; Goede, Valentin; Tresckow, Julia von; Langerbeins, Petra; Fink, Anna-Maria; Huber, Henriette; Tausch, Eugen; et al. (Journal of clinical oncology, 2024)
PURPOSE Surrogate end points are commonly used to estimate treatment efficacy in clinical studies of chronic lymphocytic leukemia (CLL). This patient- and trial-level analysis describes the correlation between progression-free survival (PFS) and minimal residual disease (MRD) with overall survival (OS) in first-line trials for CLL. PATIENTS AND METHODS First, patient-level correlation was confirmed using source data from 12 frontline German CLL Study Group (GCLLSG)-trials. Additionally, a joint-frailty copula model was fitted to validate correlation in the setting of targeted therapies (TT). Second, a meta-analysis of first-line phase III trials in CLL from 2008 to 2024 was performed. Treatment effect correlation was quantified from seven GCLLSG and nine published trials, using hazard ratios (HRs) for time-to-event and odds ratios for binary end points. RESULTS The GCLLSG analysis set comprised 4,237 patients. Patient-level correlation for PFS/OS was strong with Spearman Rho >0.9. The joint-frailty copula indicated a weak correlation for chemotherapy/chemoimmunotherapy (C/CIT) with a tau of 0.52 (95% CI, 0.49 to 0.55) while the correlation was strong for TT (tau, 0.91 [95% CI, 0.89 to 0.93). The meta-analysis set contained a total of 8,065 patients including 5,198 (64%) patients treated with C/CIT and 2,867 (36%) treated with TT. Treatment-effect correlation of the HRs for PFS and OS was R 5 0.75 (95% CI, 0.74 to 0.76, R2 5 0.56) while correlation of end-of-treatment MRD with PFS and OS was R 5 0.88 (95% CI, –0.87 to 0.89; R2 5 0.78) and 0.71 (95% CI, 0.69 to 0.73; R2 5 0.5), respectively. CONCLUSION Patient-level correlation was confirmed in the setting of TTs while treatment-effect correlation between PFS and OS remains uncertain. MRD response status showed a high treatment-effect correlation with PFS but not OS, with the caveat of a limited number of randomized trials with available MRD data.